A high‐throughput LC‐MS/MS screen for GHRP in equine and human urine, featuring peptide derivatization for improved chromatography. Issue 10 (24th February 2014) - Timms, Mark; Hall, Nikki; Levina, Vita; Vine, John; Steel, Rohan
<x xml:space="preserve">Abstract</x> The growth hormone releasing peptides (GHRPs) hexarelin, ipamorelin, alexamorelin, GHRP‐1, GHRP‐2, GHRP‐4, GHRP‐5, and GHRP‐6 are all synthetic met‐enkephalin analogues that include unnatural D‐amino acids. They were designed specifically for their ability to stimulate growth hormone release and may serve as performance enhancing drugs. To regulate the use of these peptides within the horse racing industry and by human athletes, a method is presented for the extraction, derivatization, and detection of GHRPs from equine and human urine. This method takes advantage of a highly specific solid‐phase extraction combined with a novel derivatization method to improve the chromatography of basic peptides. The method was validated with respect to linearity, repeatability, intermediate precision, specificity, limits of detection, limits of confirmation, ion suppression, and stability. As proof of principle, all eight GHRPs or their metabolites could be detected in urine collected from rats after intravenous administration. Copyright © 2014 John Wiley & Sons, Ltd.